Use of cluster analysis in the systematics of the algal genus Cryptomonas - Anton, Ann; Duthie, Hamish C. (National Research Council Canada, 1981)
Sixteen species and one variety of the algal genus Cryptomonas Ehrenberg were identified from a large number of samples collected from lakes, ponds, and marshes in eastern Canada and the Northwest Territories. A description, including photographs and drawings, is given for each taxon. Cluster analysis statistics were used to determine the taxonomic value of certain characters and the affinities between the species. It was found that binary (two-state) characters gave a more realistic diagnosis than quantitative (continuous) data because of the large variation and overlap in measurements of the latter. The following characters were considered to be of taxonomic significance in separating the species: (i) cell shape and size, (ii) number of chloropasts, (iii) number and position of chloroplasts, (iv) flagella and gullet system, and (v) number and position of other included bodies. Based on these characters, a new taxonomic key was constructed for the identification of the common freshwater species of Cryptomonas.